Feasibility and safety of a symptom-based strategy to discontinue infection control precautions for patients hospitalised with COVID-19 – a retrospective study - Grandmaison, Gaël; Baumberger, Marine; Pellaud, Charlotte; Erard, Véronique; Chuard, Christian (International Journal of Infection Control, 2021)
Background: Various recommendations exist concerning the discontinuation of contact and droplet precautions (CDP) for patients hospitalised with coronavirus disease 2019 (COVID-19). Some are based on repeated negative real-time polymerase chain reaction (RT-PCR) results, whereas other are based on clinical criteria. The feasibility and safety of these recommendations are poorly documented. Method: We conducted a retrospective study to assess the feasibility and safety of a symptom-based strategy to discontinue CDP for patients hospitalised with COVID-19. We reviewed the clinical charts of all symptomatic patients hospitalised in our institution with RT-PCR-confirmed COVID-19 to assess the application of a symptom-based strategy for the implementation and discontinuation of CDP. The patients with discontinuation of CDP in accordance with the symptom-based strategy were cross-referenced with patients with potential hospital-acquired COVID-19 in order to assess the safety of this strategy. Results: Among the 147 patients included in our study, our symptom-based strategy was respected in 95 cases (64.6%). Discontinuation of CDP in accordance with the recommendations occurred in 39 patients (26.5%). After the discontinuation of CDP, patients remained hospitalised for a median time of 18 days, with exposure to a median number of three patients, resulting in a total number of 588 days ‘patient-day-exposition’. No hospital-acquired COVID-19 was detected in contact patients. Discussion: The use of a symptom-based strategy to discontinue CDP is applicable and safe. This symptom-based strategy was applicable regardless of patient’s age or COVID-19 severity.